The Development of the Right to Public Participation in Environmental Matters as a New Concept of Administrative Decision Making in Serbia - Mirjana DRENOVAK-IVANOVIC (Transylvanian Review of Administrative Sciences, 2015)
In recent years, environmental law and pol-icy have undergone a change of governance models, shifting from central state, top-down regulation to more transparent, local decision making structures involving private companies, non-governmental organizations, concerned cit-izens and interest groups. The Aarhus Conven-tion became a part of the Serbian legal system in 2009. Its provisions not only strengthen third-par-ty rights to participate, but furthermore oblige state authorities to be active in involving citizens in environmental decisions. The question arises about the extent of consequences of this devel-opment at the international level for the national legal system.Analysis of the implementation of the Gen-eral Administrative Procedural Act (GAPA) and the Law on Environmental Protection in Serbia shows that social actors used to be allowed to participate in citizen’s forums and decision mak-ing in environmental matters, and their role was important only if they were directly and individu-ally concerned. This situation changed partially in 2004 with the adoption of new laws. The article examines recent cases in which the public and public concerned were not able to participate in environmental decision making, even though the law stipulated such a possibility. The article examines the consequences of implementing a new model, where representatives of collective interests would be able to infuence environmen-tal decision making, proposed by the Draft of the new GAPA.